The relevance of the absorptive capacity in firms' innovation strategies measured via bibliometric analysis - Vlačić, Ernest (Array, 2020)
Absorptive capacity (ACAP) as a function of systematic knowledge management is widely recognized as the catalyst for successful innovation performance in firms, particularly when it comes to identifying business opportunity information from the outside world and assimilating it into a firm’s innovation process. The concept of absorptive capacity became a widely researched topic in the area of organization and management, consequently, the definition of the ACAP components, its operationalization and outcomes, is extremely heterogeneous and has greatly affected the research production on ACAP. Therefore, the question arising is: Which approach to absorptive capacity will enable it is being truly recognized as a concept at a global level, and in which areas of economy and business is ACAP most frequently encountered, particularly when it is connected to innovation processes? Based on a sample of 1288 papers within Web of Science Core Collection, this paper presents a bibliometric analysis of relevant publications on ACAP with the specific aim of gaining a deeper insight into the relevance of the impact of absorptive capacity on a firm’s innovation strategy. The results were systematized in a form of quantitative bibliographic review. The purpose of the analysis was to determine the existing level of the empirical and theoretical efforts in the research on ACAP, with a particular focus on firms and their innovation processes as well as knowledge management processes.